Fluid resuscitation in burn patients with sepsis (Perioperaciina Medicina, 2020)
Background. There are several differences between sepsis surgical patients and burn sepsis. The effects of mediators and pathogens lasts for months if burn injury is greater than 30 % TBSA. The purpose is to improve the fluid therapy regimens for burn septicotoxemia and burn sepsis.Materials and methods. The study is based on the observation of 52 patients with burn sepsis treated at the Kyiv City Clinical Hospital No. 2 during 2017–2019. The patients were divided into three groups: first group received Ringer lactate, sodium chloride and other iso-osmolar solutions, second group – Ringer lactate + Reosorbylact at a dose of 10 ml/kg per day, third group – Ringer lactate + Reosorbylact at a dose of 15 ml/kg per day.Result. Patients received plasma to correct the wrapping system, 20 % albumin was administered when total protein level was below 50g/l. Daily use of Reosorbylact at a dose of 10–15 ml/mg helped to reduce the number of leukocytes, leukocyte intoxication index, low molecular weight metabolites (urea and creatinine), as well as the content of MSM in plasma (1.6 times), and reduce the activity of AST and ALT, lowering the level of CRР. During the observation in patients of groups 2 and 3 there was a significantly lower heart rate than in the group of crystalloids (P = 0.002), as well as higher mean blood pressure (P = 0.03), an increase in diuresis. The 24-hour fluid balance in the patients of the study groups was respectively: 64 ml/kg; 60 ml/kg and 52 ml/kg. Septic shock developed in 15.7 %, 11.8 % and 12.5 % patients of the study groups. Patients had a shorter duration of treatment with vasopressors (2.8 ± 1.5 days vs. 4.7 ± 1.4 days).Conclusions:The use of reosorbylact for patients with burn sepsis has led to a decrease in the overall fluid balance during the day.The incidence of septic shock decreased by 3.9 % and 3.2 % in the groups where Reosorbylact was used, the duration of vasopressor treatment decreased by 0.4 and 1.9 days.The detoxication and hemodynamic effect of Reosorbylact has been proved.A dose-dependent effect of Reosorbylact was observed.The study had some limitations. Thus, the conclusion of the study needs further study with more sampling
Keywords: burns; sepsis; intoxication; hemodynamic disorders; Reosorbylact